Ideas e ideales en el pensamiento de Kant. Proyección de estas nociones en su filosofía práctica - Molina Jiménez, Carlos (2005)
The gnoseological statute of Kantian concepts of idea and ideal is examined, as well as their epistemological function and, specifically, the role they perform on the author’s practical philosophy. Lastly it is node a critical appraisal of these elements enlightened by certain contemporanean thinker’s contributions.